Modelling atmospheric behaviour over southern West Africa using RegCM 4.7.1: case assessment of relative humidity and zonal wind profiles based on the 2016 DACCIWA summertime field campaign - Aryee, J. N. A.; Attoh, Emmanuel M. N. A. N.; Yamba, E. I.; Davies, P.; Amekudzi, L. K. (Elsevier, 2024)
In this paper, we present an analysis of summertime atmospheric simulation (June–July 2016) for southern West Africa (sWA) using the RegCM 4.7.1 regional climate model to describe the atmospheric behaviour over the region, and also engage comparisons between the modelled data and observed upper air data acquired during the DACCIWA (Dynamics–Aerosol–Chemistry– Cloud Interactions in West Africa) field campaign period. First, assessments of relative humidity and zonal wind profiles were made for selected coastal and inland stations, to infer the relative vertical and temporal atmospheric differences for both locations. Thereafter, the model’s performance was evaluated, capturing an excessive wet bias in RH profiles of the model with accompanying reduced zonal winds at the Tropical Easterly Jet (TEJ) region and thus produces excessive upper tropospheric cloud liquid water content. Also, in the lower troposphere (particularly, the monsoon layer), RegCM 4.7.1 model captures adequate spatial differences in both RH and zonal wind profiles along the coast and inland. We judge this outcome to be a valuable contribution on the path to rendering RegCM4 a good tool for simulating atmospheric and climate dynamics in sWA.